Proposal for an Innovation Ecosystem for the Dairy Chain in Latin America (Revista científica Pensamiento y Gestión, 2022)
The objective of this paper is to propose an innovation ecosystem, in accordance with the characteristics of the dairy chain in the Latin American context. This research is based on a descriptive study through the analysis of literature on research trends in the dairy chain, the analysis of some sources and barriers to innovation, and the identification of the activities, indicators and agents that support the ecosystem proposal. As a result, an innovation ecosystem is presented for the dairy chain that contemplates the interaction between different internal and external organizations, and that facilitates the diffusion and adoption of innovations throughout the chain.